Cartilage Tissue Engineering Approaches Need to Assess Fibrocartilage When Hydrogel Constructs Are Mechanically Loaded - Alizadeh Sardroud, Hamed; Wanlin, Tasker; Chen, Xiongbiao; Eames, B. Frank (Frontiers in Bioengineering and Biotechnology, 2022)
Chondrocytes that are impregnated within hydrogel constructs sense applied mechanical force and can respond by expressing collagens, which are deposited into the extracellular matrix (ECM). The intention of most cartilage tissue engineering is to form hyaline cartilage, but if mechanical stimulation pushes the ratio of collagen type I (Col1) to collagen type II (Col2) in the ECM too high, then fibrocartilage can form instead. With a focus on Col1 and Col2 expression, the first part of this paper reviews the latest studies on hyaline cartilage regeneration within hydrogel constructs that are subjected to compression forces (one of the major types of the forces within joints) in vitro. Since the mechanical loading conditions involving compression and other forces in joints are difficult to reproduce in vitro, implantation of hydrogel constructs in vivo is also reviewed, again with a focus on Col1 and Col2 production within the newly formed cartilage. Further, mechanotransduction pathways that may be related to the expression of Col1 and Col2 within chondrocytes are reviewed and examined. Two recently-emerged, novel approaches of load-shielding and synchrotron radiation (SR)-based imaging techniques are also discussed and highlighted for future applications to the regeneration of hyaline cartilage. Going forward, all cartilage tissue engineering experiments should assess thoroughly whether fibrocartilage or hyaline cartilage formed.